Application of stem cells combined with biomaterial in the treatment of intervertebral disc degeneration - Liu, Zongtai; Bian, Yuya; Wu, Guangzhi; Fu, Changfeng (Frontiers in Bioengineering and Biotechnology, 2022)
As the world population is aging, intervertebral disc degeneration (IDD) is becoming a global health issue of increasing concern. A variety of disc degeneration diseases (DDDs) have been proven to be associated with IDD, and these illnesses have great adverse effects on both individuals and society. The application of stem cells in regenerative medicine, such as blood and circulation, has been demonstrated by numerous studies. Similarly, stem cells have made exciting progress in the treatment of IDD. However, due to complex anatomical structures and functional requirements, traditional stem cell injection makes it difficult to meet people’s expectations. With the continuous development of tissue engineering and biomaterials, stem cell combined with biomaterials has far more prospects than before. The purpose of this review is to objectively and comprehensively summarize the development of stem cells combined with contemporary biomaterials, and the difficulties that need to be overcome.